IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK SIKAP NASIONALISME PADA SISWA SMPN 1 TOMPOBULU BANTAENG - Hasyim, Muhammad Anas (Jurnal Riset Guru Indonesia, 2023)
The purpose of this study was to determine the implementation of character education in forming an attitude of nationalism in students of SMP Negeri 1 Tompobulu Bantaeng Regency. The indicators measured in this study are the attitude of nationalism and the formation of an attitude of nationalism. This type of research is a qualitative research with a descriptive approach. The research was conducted at Tompobulu Public Middle School 2, Tompobulu District, Bantaeng Regency, in South Sulawesi Province. This research lasted for approximately 2 months. The instruments used in this study were observation sheets on the implementation of character education, interview guidelines, and documentation. The results of this study indicate that the implementation of the role of character education in forming an attitude of nationalism in students of SMP Negeri 1 Tompobulu Bantaeng, namely through Civics and Religion subjects as well as extracurriculars and each lesson is given about character education, nationalism, always being polite to parents and other people. another, having tolerance towards people with the aim of becoming the next generation who can make the Indonesian nation better.